The Influence of E-Service Quality on Repurchase Intention Through Customer Satisfaction Among Tokopedia Users in Depok City - Dea Natrilia; Dwi Rachmawati; Yupiter Yancik (Neo Journal of economy and social humanities, 2025)
This study aims to analyze the influence of e-service quality on repurchase intention through customer satisfaction among Tokopedia users in Depok City. In today’s highly competitive digital era, the quality of electronic services has become one of the key factors influencing consumers’ intention to make repeat purchases in online shopping platforms. This research applies a causal associative research design with a quantitative approach. Data were collected through an online questionnaire using Google Forms, distributed to 100 Tokopedia users residing in Depok. The data were analyzed using the Partial Least Squares – Structural Equation Modeling (PLS-SEM) technique with the SmartPLS 4.0 software. The results show that e-service quality has a significant influence on both customer satisfaction and repurchase intention. Moreover, customer satisfaction also significantly affects repurchase intention and is proven to partially mediate the relationship between e-service quality and repurchase intention. A Variance Accounted For (VAF) value of 77.4% indicates that customer satisfaction is a strong mediator in strengthening the effect of electronic service quality on consumer repurchase intention. This study highlights the importance of improving overall electronic service quality to enhance customer satisfaction and consequently encourage repeat purchases.